2018
DOI: 10.19080/jaicm.2018.07.555710
|View full text |Cite
|
Sign up to set email alerts
|

Admission Patterns and Outcomes in an Adult Intensive Care Unit in Medical Patients in Karachi

Abstract: Aims: To Review the outcome of adult admitted patients in Intensive Care Unit (ICU) in Karachi Methods: Retrospective study, clinical diagnosis, management and response of adult patients in ICU of KDLB Ziauddin hospital Karachi from January 2017 to June 2017 were studied.Results: 241 adults were admitted to the ICU with male to female ratio of 51% to 49%. Diagnoses included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
2
2
0
Order By: Relevance
“…Others were Cellulitis 0.8%, , Hypertensive Crisis 4.1%, Arrhythmias 0.8%, Diabetes with complication 2.5%, Carcinoma 0.4%, 2.1% Tb with complication, GI Bleed 3.3%, Heat stroke 0.4%, Poisoning 3.3%, Shock 1.2%, , and 0.4% (related to medical issues). 11 Another study was also consistent with our study where the most common specific diagnosis at ICU admission was all types of myocardial infarction 19% followed by Heart failure 11.1%, ARDS 8.9%, septic shock 7.3% and HIV infection 5% of the all admissions. 10 Surgical patients were the most admitted patients in the ICU mainly post operative cases of peritonitis, post operative monitoring, cancer operated patients and multiple trauma patients.…”
Section: Discussionsupporting
confidence: 91%
“…Others were Cellulitis 0.8%, , Hypertensive Crisis 4.1%, Arrhythmias 0.8%, Diabetes with complication 2.5%, Carcinoma 0.4%, 2.1% Tb with complication, GI Bleed 3.3%, Heat stroke 0.4%, Poisoning 3.3%, Shock 1.2%, , and 0.4% (related to medical issues). 11 Another study was also consistent with our study where the most common specific diagnosis at ICU admission was all types of myocardial infarction 19% followed by Heart failure 11.1%, ARDS 8.9%, septic shock 7.3% and HIV infection 5% of the all admissions. 10 Surgical patients were the most admitted patients in the ICU mainly post operative cases of peritonitis, post operative monitoring, cancer operated patients and multiple trauma patients.…”
Section: Discussionsupporting
confidence: 91%
“…The above assertion was supported by some researchers who submitted that the mortality rate is lower when diseases are managed in a special ICU than in a general ICU. 16,20 2014 The average length of stay of 5.13 ± 3.42 days is comparable to the findings of Bolaji and Kolawole, 12 but lower than the findings of Koirala et al 13 This similarity to Bolaji and Kolawole could be explained by the fact that the research was carried out in a hospital in Nigeria with comparable demographics and medical facilities, whereas Koirala's study was carried out in Nepal, India.In Koirala's study, the mortality rate was 26%, while in our case it was 56.18%. Patients in their study presented early and were managed in a specialized ICU; hence, the lower mortality rate and longer stay.…”
Section: Discussionsupporting
confidence: 59%
“…This might be due to compliance with the antihypertensive drugs, as reported by several authors in the study area. 14 , 15 The gender distribution is similar to the result of Rajput et al 16 but opposite to the findings of Tesema et al 17 who noted female preponderance. Rajput et al, in their study of 241 patients admitted to the ICU during their study period, found that 51% were males while 49% were females, which is similar to our finding of 57.3% (males) and 42.7% (females).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations